Organ–preserving operations for the gun–shot thoraco–abdominal and abdominal woundings with splenic injuries - I. A. Lurin; E. M. Khoroshun; V. V. Makarov; V. V. Nehoduiko; S. A. Shipilov; Yu. V. Bunin; R. V. Saliutin (Клінічна хірургія, 2022)
Objective.To determine the expediency of the spleen–preserving operations performance for its injury due to gun–shot thoraco–abdominal and abdominal woundings.